Influence of Modifications with Ni(II), Mn(II), and Cu(II) on the Photoelectrochemical Properties of g-C3N4 Deposited Over FTO and Its Use for Degrading Pharmaceuticals in Wastewater (2024)
Currently, graphitic carbon nitrides (g-C3N4) are materials of increasing interest in the scientific community due to their stability as semiconductors and their modulable valance (VB) and conduction band (CB). However, these materials also present drawbacks, including a high rate of electron-hole recombination, low specific area, and restricted light absorption in the visible range. Modifications of g-C3N4 can change its structure and modify its electronic properties. Herein, a mild-conditions synthesis using nickel (II), manganese (II), and copper (II) was employed to form coordination compounds as a strategy to increase their absorption capability in the visible region of the electromagnetic spectrum. Additionally, as a second strategy, photoelectrodes were made by depositing these synthesized materials onto fluorine-doped oxide (FTO, which is a transparent conductor substrate), to mitigate the electron-hole recombination and improve the efficiency of photons to electrons conversion. This research work aimed to understand the effects of transition metals modification on g-C3N4. The synthesized materials were spectroscopically and electrochemically characterized. The textural properties, CB, VB, and other properties were determined, revealing the potential for degrading pharmaceuticals in wastewater, (which are recalcitrant to conventional municipal wastewater treatment processes) causing environmental harm. The proposed structure corresponds to a carbon nitride structure linked to the metal center by the lone pairs of electrons of the peripheral amines' nitrogen for the material modified with copper (II), on the contrary, the nickel (II) and manganese (II) material the metal is linked to the lone pair of electron in the tris-s-triazine nitrogen. All the materials were used to degrade pharmaceuticals in water, achieving a 55.5%, 51.8%, 55.6%, and 32,1% for Cu-g-C3N4, Mn-g-C3N4, Ni-g-C3N4, and g-C3N4 of degradation in photocatalysis and 23.7%, 18.7%, 17.5% and 21.2% for Cu-g-C3N4, Mn-g-C3N4, Ni-g-C3N4, and g-C3N4 in photoelectrocatalysis. The determination of reactive oxygen species (ROS) in the presence of ciprofloxacin confirmed the predominant role of superoxide anion radical and a minor contribution of hydroxyl radical as a degrading species. The Cu-g-C3N4 material showed the best performance at degradation of CIP by photocatalysis, subsequently, was used to make an extent of treatment with simulated hospital wastewater (SHWW).